A CASE SERIES : HYMENOPLASTY BASED ON THE TYPE OF THE TEAR OR CLEFT PREOPERATION FINDING FOR GOOD SATISFACTION POSTOPERATIVE RESULT - Ramli, Rianto Noviady; Budi, Agus Santoso (Universitas Airlangga, 2019)
Highlights: Surgical hymenoplasty technique based on the type of the tear or cleft finding preoperative for satisfaction postoperative approach yields satisfactory results. Surgical hymenoplasty technique, tailored to the specific type of hymenal tear or cleft identified preoperatively. Abstract: Introduction: To describe our surgical hymenoplasty technique based on the type of the tear or cleft finding preoperative for satisfaction postoperative. Case Illustration: Hymenoplasty was performed on 4 patient on January 2017 until March 2017, we found three patients with U-type. We performed hymenoplasty which is to create a new surface raw, on the right and left cleft to be stiched, we use a rapid absorbable suture material, with horizontal mattress technique. Discussion: No complications developed in the patients who had undergone hymenoplasty and all patients stated that the sexual intercourse they experienced was similar to the night of the initial experience. Conclusion: Our new apporach for hymenoplasty is a technique that has good results, and this is a good approach in doing hymenoplasty. A comprehensive preoperatif consultation is essential to ensure patient and surgeon satisfaction postoperatively. Preoperative evaluation of the hymenal tissue is the basis on which a surgical technique is selected. The surgical technique is determining factor for a succesful hymenorrhaphy.